Optimizing time of use (ToU) electricity pricing in regulated market - Abdullah, M. P. (Penerbit UTM Press, 2016)
Time-of-Use (ToU) electricity price for residential consumers is receiving lots of attention lately with the increment of smart meters usage among residential customers. ToU prices reflect the actual electricity cost and the rate is commonly set base on market price of electricity. Implementing ToU pricing system on a regulated electricity system such as in Malaysia is complicated due to non existence of electricity market. The electrical utility company or the regulator will need to determine the optimum ToU prices that would give the correct price signal so that customers will react accordingly. Many factors need to be considered such as impact on electricity generation cost, load profile, load elasticity and customers’ satisfaction. This paper presents an optimization method to estimate the optimum ToU prices for given electricity demand profile and demand elasticity. The presented method able to reduce the gap between peak and off-peak demand and ensure the estimated ToU prices are fairly proportionate among hours i.e. summation of rate increments (from the fixed price) is equal to the summation of rate decrements. A simple system is used as a case study to demonstrate the application of the optimization method presented.